THE IMPACT OF STOCK SPLIT ANNOUNCEMENT ON TRADING VOLUME, RETURN, AND STOCK PRICE IN COMPANIES IN PERIOD BEFORE AND DURING COVID-19 - Nindhya, Danastri Mahasya; Hadiprajitno, Paulus Theodorus Basuki (Diponegoro Journal of Accounting, 2024)
The purpose of this study was to determine the effect of stock split announcements on trading volume, return and stock price in companies before and during Covid-19. The research method used in this research is quantitative research method. The sample in this study were companies that announced a stock split of 36 companies. The method of determining the sample using purposive sampling technique. This study uses a statistical analysis test of two sample tests with a 15-day observation period is t = -7 (7 days before stock split), t = 0 (event date) and t = +7 (7 days after stock split). The data analysis method used in this study is the Wilcoxon Signed Ranks Test. The results of this study indicate that there is a statistically significant difference in the average TVA before and after the announcement in the period before and during Covid-19. While there is no statistically significant difference in the average return and stock price before and after the announcement in the period before and during Covid-19.